Cycles in cattle and hog prices in South America - Astrid Fliessbach; Rico Ihle (Australian Journal of Agricultural and Resource Economics, 2020)
Prices of agricultural products often vary in relatively stable patterns around their long-run trends. These variations translate into fluctuations of selling prices as well as farm revenues. We provide an overview of the current literature on agricultural price cycles. Using a transparent and reproducible model selection process and the Kalman filter, we select optimal models and estimate the cyclic patterns of hog and cattle prices for Brazil, Chile and Uruguay. Durations of those cycles are found to be about three years and seven years, respectively. These durations are in line with the literature and the biological characteristics of livestock production. Our results can inform producers forecasts on price developments in the short and medium run. They are useful for guiding policy makers on the timing of policy interventions for influencing the duration or the amplitudes of cycles.
Keywords: 330; cattle cycle; Kalman filter; pork cycle; price fluctuations; state-space models